Simulation Platform Development for Diabetes and Technology Self-Management. (November 2022) - Faulds, Eileen R.; Rayo, Michael; Lewis, Claudia; Noble, Carl W; Gifford, Ryan; Happ, Mary Beth; Joyce, Lilly; Dungan, Kathleen
Background: Specialized education is critical for optimal insulin pump use but is not widely utilized or accessible. We aimed to (1) test the usability and acceptability of A1Control, a simulation platform supporting insulin pump education, and (2) determine predictors of performance. Method: Rural adult insulin pump users with type 1 diabetes (T1D) participated in a mixed methods usability study in 2 separate rounds. Participants navigated 3 simulations (ie, infusion site occlusion, hypoglycemia, exercise). Net Promoter Score (NPS) and Systems Usability Scale (SUS) were administered. Semi-structured interviews and direct observation were used to assess perceived usability, acceptability and performance. Synthetic Minority Oversampling Technique was used to fit predictive models for visualization of patterns leading to good or poor A1Control performance. Results: Participants ( N  = 13) were 28-70 years old, 10 used automated insulin delivery and 12 used continuous glucose monitoring (CGM). Mean NPS was 9.5 (range 9-10) and positive sentiment during interviews indicated very high acceptability. SUS (mean 88.5, range 70-100) indicted a high perceived usability. CGM percent wear ≥ 94%, time spent in hypoglycemia ≤ 54 mg/dl of <0.01%, and <70 mg/dl of 0.5% predicted successful site-occlusion scenario performance with 100% accuracy. BOLUS score ≥ 2, TDD ≥ 34, and technology brand predicted exercise scenario success with 100% accuracy. There were an insufficient number of failed hypoglycemia scenarios to assess predictors. Conclusion: A1Control shows potential to increase access and frequency of self-management and technology education. Additional study is needed to determine sustained engagement and benefit.